Analisa Kebutuhan Kayu Bakar bagi Masyarakat Disekitar Kawasan Hutan di Desa Noinbila Kecamatan Mollo Selatan Kabupaten Timor Tengah Selatan - Maria Charlina Isu; Ludji Michael Riwu Kaho; Fadlan Pramatana; Lusia S. Marimpan (Wana Lestari, 2024)
Their need. Problem of the firewood was urgent need seriously attention and it is needed to be researched because the community members have been taking the firewood from the forest area without caring the forest sustainability. This research objectives was to investigate the forest quality and volume of firewood taking influenced by the community consumption of firewood surround the forest at Noinbila Village, Mollo Selatan Sub-district, Timor Tengah Selatan Regency. The research found that the firewood consumption of the community reached at 211.615 SM/capita/year equals to 8,464,598 million mᶾ. There were some kind of wood taken by the community, namely Ampupu, Mahoni, Gamalin, Jati, Kasuari, Kayu Putih, Lamtoro, cashew-nut, and kabesak. The result showed that the community surround the forest at Noinbila Village using the firewood as the main priority energy for consuming and selling. This activity has an impact on decreasing of the forest quality as shown by regeneration status of the forest at Noinbila Village. It means that there were no regeneration anymore. In addition, analysis of land cover at the forest area at Noinbila Village during 2013 – 2023 found that the forest has been turning into negative point since the declining of dense vegetation as well as moderate vegetation followed by the increasing of vacant land annually. These facts will threaten the forest quality in the future.